Xanthogranulomatous cholecystitis incidental finding in laparoscopic cholecystectomy: A case report - Pasha, Mahaboob; Wani, Umer Hamid; Najar, Firdous Ahmad; Ansari, Mohammed Shakeel (Indian Journal of Case Reports, 2024)
Xanthogranulomatous cholecystitis (XGC) is a rare form of chronic cholecystitis due to the destruction and infiltration of macrophages into the gallbladder wall mimicking gallbladder carcinoma. The lack of distinguishing radiologic or clinical characteristics to differentiate from gallbladder carcinoma leads to unwanted extensive surgeries. Typically, diagnosis is confirmed by histopathology. This case report of a 51-year-old female presented with complaints of intermittent pain in the abdomen, nausea, and vomiting for 2 months with right subcostal tenderness and no palpable mass. She had undergone cholecystectomy after getting a diagnosis of chronic cholecystitis with cholelithiasis later on the histopathological study of the removed gallbladder revealed the diagnosis of XGC. This case report highlights the importance of evaluating further radiological findings and other non-invasive techniques to diagnose XGC preoperatively and prevent extensive surgeries.